(untitled) (Semiárida, 2020)
In this work, 15 species belonging to 13 genera are recorded. Keys for genera and species identification are attached. The valid name, synonyms and popular name, of each taxon, are given; also the bibliography of the first citation, iconography, distribution and frequency In La Pampa and a selected examined herbarium specimen.